Thoughts on Strengthening Safety of Rural Water Supply in the New Era-Taking Binxian County, Shaanxi Province as an Example - Liang Ji; Zhang Haitao; Qin Jinbo (MATEC Web of Conferences, 2018)
At present, our country has entered a new era. The report of the 19th National Congress of CPC pointed out that we must always put the top priority of the Party’s work on solving the problem of agriculture, rural areas and farmers. The safety of rural water supply safety is the direct and realistic interest-related problem that the rural masses most concern. In the new era, we should further strengthen the safety work of rural water supply, gradually promote the integration of urban and rural water supply, and effectively solve the increasingly serious safety-related demand of water supply of villagers and the contradiction caused by uneven and insufficient development of urban and rural water supply. Binxian County is located in the water shortage area in the west of China. The management model of "urbanizing rural water supply" that the county explored to establish has effectively solved the problem about the construction, operation and maintenance of rural water supply project. It accords with the development idea of rural water supply in the new era, and its successful experience can be duplicated and popularized in Shaanxi Province and even in the whole country.